2020
DOI: 10.1111/bpa.12897
|View full text |Cite
|
Sign up to set email alerts
|

Denser brain capillary network with preserved pericytes in Alzheimer's disease

Abstract: Pericytes are vascular mural cells that surround capillaries of the central nervous system (CNS). They are crucial for brain development and contribute to CNS homeostasis by regulating blood–brain barrier function and cerebral blood flow. It has been suggested that pericytes are lost in Alzheimer's disease (AD), implicating this cell type in disease pathology. Here, we have employed state‐of‐the‐art stereological morphometry techniques as well as tissue clearing and two‐photon imaging to assess the distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 65 publications
(95 reference statements)
4
24
0
Order By: Relevance
“…While there may likely be regional differences in cell bodies, it is possible that surface areas of pericyte cell processes are retracted or reduced in the parietal cortex in AD, but this may not reflect a change in the number of cell bodies. Our results in AD are, however, remarkably in agreement with the recent study in which 3D-stereological quantification showed increased capillary density with largely preserved pericytes in the frontal cortex [ 18 ]. Consistent with our observations, the study suggested that cortical pericyte demise is not characteristic of AD pathology although it may be different in the hippocampus [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While there may likely be regional differences in cell bodies, it is possible that surface areas of pericyte cell processes are retracted or reduced in the parietal cortex in AD, but this may not reflect a change in the number of cell bodies. Our results in AD are, however, remarkably in agreement with the recent study in which 3D-stereological quantification showed increased capillary density with largely preserved pericytes in the frontal cortex [ 18 ]. Consistent with our observations, the study suggested that cortical pericyte demise is not characteristic of AD pathology although it may be different in the hippocampus [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…This means that increasing age appears to have a stronger effect on cortical pericyte cell bodies in capillaries than any disease pathology did, either neurodegenerative or vascular of origin. Our observations suggest within the disease groups frontal cortical pericytes were overall preserved [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As OPN enhances VEGF expression in endothelial cells (Dai et al, 2009) and IGF‐1 drives the tissue repairment, including angiogenesis, in the brain (Vannella & Wynn, 2017), MyD88‐haploinsufficient microglia might prevent vascular impairment in AD brain. However, a postmortem tissue study showed a higher density of capillaries in the brain of AD patients (Fernandez‐Klett et al, 2020). Tg4510 tau‐transgenic mice display increased capillaries, but with atypical and spiraling morphologies, and reduced luminal diameter of blood vessels (Bennett et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Their expression in cultured pericytes was not altered, either, by IL‐1β at the concentrations sufficient for the down‐regulation of LRP1 expression. There was a recent study showing that the density of pericytes is reserved during AD pathogenesis (Fernandez‐Klett et al, 2020).…”
Section: Discussionmentioning
confidence: 99%